2006
DOI: 10.1353/lib.2006.0052
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis in Library and Information Science: Method, History, and Recommendations for Reporting Research

Abstract: Meta-analysis is a method for summarizing statistical fi ndings across multiple research studies. It is a useful method for assessing the level of agreement or disagreement surrounding a given research question. The ability to perform meta-analysis is dependent on the level of consistency in measures and the amount of data shared in published research. Guidelines to minimum standards for reporting research may improve the quality of writing in published research. Inconsistencies in reporting research fi ndings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In applying the method, researchers in LIS will find Saxton's article on the method (Saxton, 2006) and Ankem's (2005a) article on conducting meta-analysis to be helpful. These articles provide references for additional reading, especially seminal materials, in meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In applying the method, researchers in LIS will find Saxton's article on the method (Saxton, 2006) and Ankem's (2005a) article on conducting meta-analysis to be helpful. These articles provide references for additional reading, especially seminal materials, in meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Saxton's approach was conservative; given the paucity of data, the latter approach is recommended. Saxton's updated recommendations for meta-analyses found in an article published in Library Trends include this suggestion (Saxton, 2006).…”
Section: Synthesismentioning
confidence: 99%
“…Speaking of the value obtained through meta-analysis, Ankem notes that "the reasons and advantages for any interested researcher to conduct a meta-analysis are that it (1) allows for more precise results related to a research problem as these results are a mathematical aggregate of those from various studies examining the variables in question, and (2) increases in [statistical] power" (p. 165). Other LIS meta-analysis applications are ably summarized in Saxton's (2006) literature review.…”
Section: Meta-analytic Frameworkmentioning
confidence: 99%
“…Systematic reviews differ from meta-analyses in that the findings in a systematic review may be reported quantitatively or qualitatively, whereas meta-analyses use statistical tests to combine results across multiple research studies. 11 In building the data set to be examined, inclusion criteria must be established appropriate to the question being asked.…”
Section: Systematic Reviewmentioning
confidence: 99%